O ensino e a aprendizagem do conceito de número na perspectiva piagetiana : uma análise da concepção de professores da educação infantil - Burgo, Ozilia Geraldini (2007)
Education teachers' concept on the teaching of numbers to 4-6-year old children with reference to Piaget's Theory is investigated. Piaget and Szeminska's The Genesis of Numbers in the Child and other works comprising Piaget's concepts, especially those published in Brazil, were analyzed. Polyvalent teachers' training, especially for those dedicated to Infant Education, was also researched. Didactic knowledge of Mathematics in training courses and the teachers' concepts with regard to teaching and learning were given priority. Above theoretical presuppositions were a great help in the analysis of answers given by 10 interviewed teachers. Results show that Infant Education teachers' concepts with regard to the teaching of number are rather empiricists, although mixed with aprioristic and interactionist situations where practice prevails to the detriment of theory. Concepts are easily worn out when teachers perceive playful situations. A constructivist concept emerges when activities involving the construction of the number concept within the Piaget's perspective are developed.